Rewriting Academia The Development of the Anglicist Women's and Gender Studies of Continental Europe - Haas, Renate (Peter Lang International Academic Publishers, 2015)
From a historical perspective, the full academic establishment of Women's and Gender Studies is a radical and far-reaching innovation. Decisive impulses have come from the United States, the European unification and globalization. European Women's and Gender Studies are therefore intimately linked to the English language and Anglophone cultures, as the near untranslatability of «gender» shows. In this volume 25 experts present surveys for their countries with a historical and European contextualization and offer fundamental insights not only for English Studies but also various other disciplines.